Discovery of energy-dependent phase variations in the polarization angle of Cen X-3 - Zhao, Qing-Chang; Tao, Lian; Tsygankov, Sergey S.; Poutanen, Juri; Feng, Hua; Zhang, Shuang-Nan; Li, Hancheng; Ge, Mingyu; Zhang, Liang; Mushtukov, Alexander A. (EDP Sciences, 2026)
We present a detailed polarimetric analysis of Cen X-3 using IXPE observations during its high state, revealing a complex, energy-dependent polarization behavior. While phase-averaged polarization shows marginal energy dependence, phase-resolved analysis reveals that the energy dependence of the polarization angle is strongly phase-dependent, with dramatic variations visible in a few specific phase intervals. We modeled this behavior using a two-component polarization framework consisting of a pulsed component governed by the rotating vector model (RVM) and an additional phase-dependent component. By allowing the additional component’s polarized flux to vary with pulse phase while fixing its PA, the observed complex behavior can be reconciled with a single set of RVM parameters across all energies. Spectroscopic analysis using IXPE, NICER, and NuSTAR during the high state reveals phase-modulated intrinsic hydrogen column density and covering fraction, suggesting that the wind properties are modulated with pulse phase. Our findings indicate that phase-dependent scattering in the disk wind may significantly alter the observed polarization properties of X-ray pulsars.